How Finnish and Portuguese Parents’ Implicit Beliefs About Learning Actualize at Home - Levinthal, Cristiana; Kuusisto, Elina; Tirri, Kirsi (Frontiers in Education, 2021)
The purpose of this qualitative study was to explore parental engagement in the home-learning environment, and parents’ implicit beliefs about learning underlying such engagement. Nineteen parents of elementary school children between seven and twelve years old were interviewed in two different cultural contexts, Finland (N = 10) and Portugal (N = 9). The interviews were subjected to inductive and deductive content analysis. Forms of parental engagement at home were similar in both countries, divided between two main categories: engagement with the child’s holistic development and engagement with the child’s schooling process. Parental narratives about engagement were, for the most part, embedded in a growth mindset (or an incremental meaning system). The most common actualizations of engagement included considering the child’s learning contexts and emotions; encouraging effort, persistence and practice; approaching difficulties as a natural part of learning and suggesting strategies for overcoming them. Parental practices of engagement were combined with the actualization of their implicit beliefs to create engagement–mindset parental profiles. Twelve parents were classified as having a Growth mindset to support the child’s holistic development profile, and the other seven were distributed amongst the three remaining profiles. The study contributes to the growing interest on the association between parental engagement and their learning-related implicit beliefs, giving clear first-person illustrations of how both occur and interact in the home-learning environment. Implications for practice are discussed.